Longitudinal Monitoring Reveals Persistence of Colistin-Resistant Escherichia coli on a Pig Farm Following Cessation of Colistin Use - Khine, Nwai Oo; Lugsomya, Kittitat; Niyomtham, Waree; Pongpan, Tawat; Hampson, David J.; Prapasarakul, Nuvee (Frontiers in Veterinary Science, 2022)
Colistin-resistant bacteria harboring plasmid-mediated mcr genes are of concern as they may be a cause of serious nosocomial infections. It is hypothesized that cessation of colistin use as a feed additive for pigs will reduce the occurrence and distribution of mcr genes in farms. The aim of this study was to investigate this hypothesis by longitudinal monitoring and characterizing of mcr positive Escherichia coli (MCRPE) isolates after colistin was withdrawn on a central Thailand pig farm that previously had a high frequency of MCRPE. Colistin use ceased at the beginning of 2017, and subsequently 170 samples were collected from farrowing sows and suckling piglets (n=70), wastewater (n=50) and farm workers (n=50) over a 3.5-year period. Bacteria were identified by MALDI-TOF mass spectrometry and minimal inhibitory concentrations were determined by broth microdilution. The antibiogram of mcr positive E. coli isolates was determined using the Vitek2 automated susceptibility machine, and multiplex and simplex PCRs were performed for mcr-1-8 genes. MCRPE containing either mcr-1 or mcr-3 were isolated from pigs throughout the investigation period, but with a declining trend, whereas MCRPE isolates were recovered from humans only in 2017. MCRPE were still being recovered from wastewater in 2020. Most MCRPE isolates possessed the virulence genes Stap, Stb, or Stx2e, reflecting pathogenic potential in pigs, and showed high rates of resistance to ampicillin, gentamicin and tetracycline. Pulsed-field gel electrophoresis and multi-locus sequence typing showed that diverse MCRPE clones were distributed on the farm. The study identified a decline of pathogenic MCRPE following withdrawal of colistin, with pigs being the primary source, followed by wastewater. However, short-term therapeutic usage of other antibiotics could enhance the re-occurrence of mcr-carrying bacteria. Factors including the environment, management, and gene adaptations that allow maintenance of colistin resistance require further investigation, and longer-term studies are needed.